Longitudinal evaluation of breaststroke spatial-temporal and coordinative parameters: Preparing of the 100-m-breastroke bronze medallist of the Athena 2004 Olympic Games - Seifert, L.; Chollet, D.; Papparodopoulos, C.; Guerniou, Y.; Binet, G. (Biomechanics and Medicine in Swimming X, 2006)
This study shows how a model of arm to leg coordination in the breaststroke was used to prepare the 2004 French national champion in the 50-m, 100-m and 200-m breaststroke for the Athens 2004 Olympic Games. His coordination was periodically evaluated and the detailed Information provided by this model served to guide the subsequent training decisions. Seven evaluations were made over a two-year period and assumed a parallel with the competitive performances during this period. At each evaluation, the swimmer swam 25-m at his 100-m race pace and the spatial-temporal parameters (velocity, stroke rate and stroke length) and coordination (temporal gaps between the stroke phases of the arm and leg: T1a, T1b, T2, T3 and T4) were calculated over three stroke cycles identified from under-water cameras with lateral and frontal views.